Promoting Social Inclusion by Gender and Disability: Insights from Rupani Rural Municipality, Saptari, Madhesh Province - Bhujel, Indra Bahadur (Journal of Social Protection, 2024)
This paper analyses policies and practices related to Gender, Equality, Disability, and Social Inclusion (GEDSI) in Nepal’s federal governance systems. Social inclusion in Nepal, enshrined in the Constitution and subsequent policy provisions, has progressively evolved as a key development strategy, particularly emphasizing gender and disability rights through affirmative action’s and sect oral integration. This paper draws on review of policies and a descriptive research design. Secondary data were collected from the review of literature and. Lack of data with adequate disaggregation, on intersectionality, and limited capacity at the local level hinder evidence-based planning and inclusive budgeting. Additionally, issues like child marriage, restricted decision-making roles for women, and inadequate male engagement further challenge women’s empowerment. This paper concludes that GEDSI has been reflected in policies, programmes, and budgets; however, there remains a lack of clear mechanisms to identify interventions and reach the most excluded within the marginalised groups. The paper highlights the urgent need for disaggregated data systems, mandatory GEDSI-responsive budgeting and monitoring tools, sector-specific guidelines, and provision of accessible infrastructure.